Nanocápsulas de poli(ɛ-caprolactona) contendo vimpocetina: desenvolvimento e avaliação da atividade anticonvulsivante - Rosa, Carolina Pires (2017)
Epilepsy is a disease characterized by convulsive seizures, caused by an excessive neuronal electrical discharge, which affects 50 million people worldwide. Vinpocetine, derived from the alkaloid vincamine, is a neuroprotective that has antioxidant activity, being used in the treatment of neurodegenerative diseases. Researches have also shown an important antiepileptic activity for vinpocetine. However, this drug presents low solubility and short half-life, limiting its application in the pharmaceutical field. Thus, nanocapsules, which are also well researched for the cerebral delivery of drugs, become alternatives to deliver this active substance. In this work, vinpocetine-loaded poly(ɛ-caprolactone) (PCL) nanocapsule suspensions (0.5 mg/mL) were developed by the interfacial deposition of preformed polymer, containing medium chain triglycerides (NC-TCM-VP) or avocado oil (NC-ABA-VP) as core, in order to evaluate the physicochemical characteristics, drug release profile, both in vitro antioxidant and in vivo anticonvulsive activities of the drug associated with nanostructures. The nanocapsule suspensions had a size of 200 to 211 nm (Zetasizer®), PdI of 0.12 to 0.13, negative zeta potential, pH between 6.78 to 6.83, drug content close to 95% and encapsulation efficiency about 98 %. In the parameters evaluated, the type of oil influenced the viscosity of the formulations (capillary viscometer) and particle size distribution (Mastersizer®). Atomic force microscopy of the formulations demonstrated the presence of colloidal particles with shape close to spheres. Both developed systems were able to control the release of vinpocetine, compared to the free drug, by the dialysis bag diffusion technique using phosphate buffer pH 7.4: ethanol (70:30). The suspensions prepared with TCM presented better stability as well as a more homogeneous size distribution compared to avocado oil, and were then selected to follow the studies. The NC-TCM-VP formulations showed higher in vitro antioxidant activity than the free drug, by the TBARS method, as well as suspensions without drug. In the in vivo study, using animal model of seizure induced by pentylenetetrazole (PTZ), doses of 5 mg/kg or 10 mg/kg vinpocetine were evaluated, and treatments were performed 30 minutes or 4 h prior to administration of PTZ. The results demonstrated that NC-TCM-VP suspensions were able to improve the antiepileptic effect of the free drug or vehicle/nanocapsules without drug in some parameters evaluated, mainly in the shortest time (30 minutes). In view of the results obtained, nanocapsule suspensions are promising aqueous systems for the cerebral delivery of vinpocetine, a highly lipophilic drug, and may be a future alternative for the treatment of epilepsy. Vinpocetine is not yet used clinically for this purpose.